Targeting SphK2 Reverses Acquired Resistance of Regorafenib in Hepatocellular Carcinoma - Shi, Weiwei; Zhang, Shan; Ma, Ding; Yan, Dongliang; Zhang, Guang; Cao, Yin; Wang, Zhongxia; Wu, Junhua; Jiang, Chunping (Frontiers in Oncology, 2020)
Background: Regorafenib is a second-line therapy drug used for advanced hepatocellular carcinoma (HCC). Unfortunately, the survival benefit of the patients receiving this treatment is modest, which may be attributed to drug resistance. In the present study, sphingosine kinase 2 (SphK2) was targeted to reverse regorafenib resistance in HCC. Methods: The functions of SphK2 and sphingosine-1-phosphate (S1P), the catalytic product of SphK2 in regorafenib resistance of HCC cells, were evaluated by cell counting kit-8 assay, colony formation, cell cycle evaluation, and annexin V–fluorescein isothiocyanate/propidium iodide double-staining assay. The antitumor activity of combined treatment of regorafenib and the SphK2-specific inhibitor ABC294640 was examined in HCC cells in vitro and xenograft model in vivo. The molecular mechanisms of SphK2/S1P-mediating regorafenib resistance were investigated using cell line establishment and Western blot analysis. Results: Well-developed regorafenib-resistant HCC cells indicated high expression levels of SphK2. The sensitivity to regorafenib of regorafenib-resistant HCC cells was restored following SphK2 knockdown or pharmacological inhibition by ABC294640. In addition, ectopic expression of SphK2 and exogenous addition of S1P decreased the sensitivity of HCC cells to regorafenib. Furthermore, the combination treatment with ABC294640 sensitized resistant tumor to regorafenib in xenograft model of HCC. The phosphorylation levels of nuclear factor κB (NF-κB), as well as those of signal transducer and activator of transcription 3 (STAT3), were positively associated with SphK2 and S1P. Conclusions: SphK2/S1P mediates regorafenib resistance of HCC through NF-κB and STAT3 activation. Targeting SphK2 by ABC294640 potently reduces regorafenib resistance of HCC cells both in vitro and in vivo. The combination of ABC294640 and regorafenib could be developed as a novel potential treatment strategy for advanced HCC.